2019
DOI: 10.3389/fimmu.2019.01573
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Potential Immune Checkpoint Member HHLA2 in Human Tumors: A Comprehensive Analysis

Abstract: Immunological checkpoint inhibitors have been immensely successfully applied in the treatment of cancer, however, a portion of tumor patients can't benefit from checkpoint therapy. The low PD-1/CTLA-4 positive rate and involvement of multiple immunosuppressive pathways are thought to be one of the reasons for treatment failure in non-responding patients. A new immune checkpoint molecule, HHLA2, which was widely expressed in PD-1 negative human tumors, may be a promising target for the improvement of recent imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 49 publications
3
37
0
Order By: Relevance
“…We examined the correlation between the expression levels of the 42 differentially expressed lncRNAs and each differentially expressed mRNA using two-sided Pearson correlation coefficients and the z-test. The mRNAs positively or negatively correlated with the 42 lncRNAs were considered to be lncRNA-related mRNAs (|Pearson correlation coefficient| > 0.4 [16][17][18][19][20] and P-value <0.05). The lncRNA-mRNA co-expression network was then constructed using Cytoscape V.3.8.5 (https://cytoscape.org/).…”
Section: Construction Of Co-expression Networkmentioning
confidence: 99%
“…We examined the correlation between the expression levels of the 42 differentially expressed lncRNAs and each differentially expressed mRNA using two-sided Pearson correlation coefficients and the z-test. The mRNAs positively or negatively correlated with the 42 lncRNAs were considered to be lncRNA-related mRNAs (|Pearson correlation coefficient| > 0.4 [16][17][18][19][20] and P-value <0.05). The lncRNA-mRNA co-expression network was then constructed using Cytoscape V.3.8.5 (https://cytoscape.org/).…”
Section: Construction Of Co-expression Networkmentioning
confidence: 99%
“…Then, the TF-PMP network shows that transcription factors FOXM1, NCAPG, CENPA, MYBL2, EOMES, IRF4, IKZF1 and BATF are closely related to these PMPs. Some previously studies have shown those TFs were connected with occurrence and progression of ccRCC [12][13][14][15][16][17][18]. Base on the above ndings, we have good reason to believe that those PMPs play a signi cant role in ccRCC as a whole.…”
Section: Discussionmentioning
confidence: 52%
“…[ 59 ] A comprehensive analysis to evaluate the prognostic significance of HHLA2 in human pan-cancer suggested that HHLA2 is an independent predictive factor for prognosis of many human tumors. [ 60 ] Unfortunately, this comprehensive study did not indicate the prognostic value in lung cancer. In an independent study on NSCLC, the patients with high HHLA2 expression tended to have a poorer survival, but this was not statistically significant.…”
Section: Co-stimulatory T Lymphocyte Checkpointsmentioning
confidence: 96%